Transducer‐based evaluation of tremor. Issue 9 (6th June 2016) - Haubenberger, Dietrich; Abbruzzese, Giovanni; Bain, Peter G.; Bajaj, Nin; Benito‐León, Julián; Bhatia, Kailash P.; Deuschl, Günther; Forjaz, Maria João; Hallett, Mark; Louis, Elan D.; Lyons, Kelly E.; Mestre, Tiago A.; et al.
ABSTRACT: The International Parkinson and Movement Disorder Society established a task force on tremor that reviewed the use of transducer‐based measures in the quantification and characterization of tremor. Studies of accelerometry, electromyography, activity monitoring, gyroscopy, digitizing tablet‐based measures, vocal acoustic analysis, and several other transducer‐based methods were identified by searchingPubMed.gov . The availability, use, acceptability, reliability, validity, and responsiveness were reviewed for each measure using the following criteria: (1) used in the assessment of tremor; (2) used in published studies by people other than the developers; and (3) adequate clinimetric testing. Accelerometry, gyroscopy, electromyography, and digitizing tablet‐based measures fulfilled all three criteria. Compared to rating scales, transducers are far more sensitive to changes in tremor amplitude and frequency, but they do not appear to be more capable of detecting a change that exceeds random variability in tremor amplitude (minimum detectable change). The use of transducer‐based measures requires careful attention to their limitations and validity in a particular clinical or research setting. © 2016 International Parkinson and Movement Disorder Society